THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Nabila, Siti; Anwar, Syaiful; Fitriani, Dhea; Ismayanti, Rahmania; Fauziah, Syifa (CV. Four Son Scholarship, 2024)
Organizational culture becomes an identity of a company. A good culture will have a positive impact on employee performance. This also applies when there is high employee motivation within a company. High employee motivation leads to improved employee performance. This research involved all 80 employees of PT Crea Cipta Cemerlang by distributing questionnaires to them. The sampling technique used was the study population, and the data were analyzed using SPSS version 16.0 with the multiple linear regression method. The results show that organizational culture and work motivation simultaneously influence employee performance. Organizational culture and work motivation also have a partial influence on performance. Organizational culture is a more dominant variable influencing employee performance compared to the motivation variable